2006
DOI: 10.1166/jnn.2006.510
|View full text |Cite
|
Sign up to set email alerts
|

Development of an Amperometric Ethanol Biosensor Based on a Multiwalled Carbon Nanotube-Nafion-Alcohol Dehydrogenase Nanobiocomposite

Abstract: An amperometric biosensor for the determination of ethanol has been constructed. It comprises a multiwalled carbon nanotubes (MWNTs) conduit, a Nafion binder, and an alcohol dehydrogenase (ADH) function. The measurement of ethanol is based on the signal produced by beta-nicotinamide adenine dinucleotide (NADH), the product of the enzymatic reaction. The MWNTs are cylindrical with an outer diameter in the range 40-60 nm, an inner diameter in the range 2-5 nm, and a length of up to several micrometers. The homog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 0 publications
0
19
0
Order By: Relevance
“…Enzymatic biofuel cells can also electrochemically detect a wide range of substrates from simple alcohols to macromolecules such as immunoglobulins. 25,[58][59][60][61] …”
Section: Analytical Applications Of Biofuel Cellsmentioning
confidence: 99%
“…Enzymatic biofuel cells can also electrochemically detect a wide range of substrates from simple alcohols to macromolecules such as immunoglobulins. 25,[58][59][60][61] …”
Section: Analytical Applications Of Biofuel Cellsmentioning
confidence: 99%
“…A lot of materials have been used to fabricate tyrosinase-based biosensor, for example, alumina sol-gel [15], polythiophene [16], graphite-Teflon composite [17], and chitosan [18]. Recently, the development in the field of MWNTNafion composite film applied to electroanalysis has opened a new range of possibilities for the construction of electrochemical biosensors based on these materials [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Depending on CNTs electrochemical properties, the CNTs-based sensors can be used for detecting NADH, hydrogen peroxide at a lower working potential [19,21,30]. Recent studies demonstrated improved electrochemical responses of ethanol and glucose determination at MWNT-Nafion nanocomposite film modified electrode [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Many polymers have been reported for such applications, including nafion (Fortier et al, 1992;Vaillancourt et al, 1999) , polypyrrole (Branzoi & Pilan 2008;Ekanayake et al, 2007), polytyramine (Situmorang et al, 1999) and silicate sol-gels (Llaudet et al, 2005;Rickus et al, 2002;Salimi et al, 2004). Nafion is a negatively charged sulfonated tetrafluorethylene copolymer, which possesses a strong surface adhesion to electrode surface and a low swelling capability in aqueous media (Gong et al, 2005;Liaw et al, 2006;. Thus, nafion is quite appropriate for enzyme immobilization.…”
Section: Enzyme Immobilization Approachesmentioning
confidence: 99%